2022
DOI: 10.3847/1538-4365/ac9966
|View full text |Cite
|
Sign up to set email alerts
|

H-AMR: A New GPU-accelerated GRMHD Code for Exascale Computing with 3D Adaptive Mesh Refinement and Local Adaptive Time Stepping

Abstract: General relativistic magnetohydrodynamic (GRMHD) simulations have revolutionized our understanding of black hole accretion. Here, we present a GPU-accelerated GRMHD code H-AMR with multifaceted optimizations that, collectively, accelerate computation by 2–5 orders of magnitude for a wide range of applications. First, it introduces a spherical grid with 3D adaptive mesh refinement that operates in each of the three dimensions independently. This allows us to circumvent the Courant condition near the polar singu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 127 publications
2
43
0
Order By: Relevance
“…This problem can be solved if a smaller precessing disk tears of from a larger nonprecessing disk due to the differential frame dragging (Lense & Thirring 1918) of spacetime by a spinning BH. This process, called disk tearing, was observed in various smoothed particle hydrodynamics (SPH) simulations (e.g., Nixon et al 2012aNixon et al , 2012bNealon et al 2015; and recently confirmed by GRMHD simulations (Liska et al 2021(Liska et al , 2022b. Disk tearing, interstingly, also leads to a rapid burst of accretion, possibly explaining the large luminosities and spectral swings observed in accreting BHs (e.g., Nixon & Salvesen 2013;.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…This problem can be solved if a smaller precessing disk tears of from a larger nonprecessing disk due to the differential frame dragging (Lense & Thirring 1918) of spacetime by a spinning BH. This process, called disk tearing, was observed in various smoothed particle hydrodynamics (SPH) simulations (e.g., Nixon et al 2012aNixon et al , 2012bNealon et al 2015; and recently confirmed by GRMHD simulations (Liska et al 2021(Liska et al , 2022b. Disk tearing, interstingly, also leads to a rapid burst of accretion, possibly explaining the large luminosities and spectral swings observed in accreting BHs (e.g., Nixon & Salvesen 2013;.…”
Section: Introductionmentioning
confidence: 79%
“…In this work we utilize the radiative version of our GPU accelerated GRMHD code H-AMR (Liska et al 2018(Liska et al , 2022b. H-AMR evolves the ideal GRMHD equations and radiation transfer equations in addition to the electron and ion entropies.…”
Section: Numerical Setupmentioning
confidence: 99%
See 3 more Smart Citations